Experimental and numerical study on cavitation performances of a turbopump with and without an inducer. (May 2022) - Fu, Yanxia; Xie, Jiangfeng; Shen, Yang; Pace, Giovanni; Valentini, Dario; Pasini, Angelo; D'Agostino, Luca
The cavitation performances and its internal flows in a centrifugal turbopump with and without a three-bladed axial inducer have been studied both experimentally and numerically. A 3D steady numerical model has been applied to simulate the cavitating flow from the inlet to the outlet ducts of the turbopump with and without an inducer by using ANSYS CFX code. In the present work, to clarify this relationship, we conducted experiments in both cold water ( T = 20°C) and hot water ( T = 80°C) with a focus on the development of vapor volume fraction and head degradation by gradually reducing the inlet pressure from atmospheric conditions to the minimum allowable value at a constant rate of about 3 mbar/s. The measured and predicted cavitation performances of the turbopump with and without an inducer have been compared under different operating conditions and the temperature of the operating fluid.